High-temperature-resistant grouting and water plugging material for underground engineering and preparation method thereof
By using a double-liquid grouting material of components A and B in underground engineering grouting water blocking materials, combined with the design of retarded expansion particles, the problems of easy condensation and poor high temperature resistance in high temperature environments are solved, and the effective water blocking effect in long-distance transportation and high temperature environments are achieved.
Patent Information
- Application Number
- CN202510353320.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-25
AI Technical Summary
The existing underground engineering grouting water blocking materials are prone to condense in high-temperature environments, affecting the conveying effect, and have poor high temperature resistance, which cannot meet the water blocking needs in long-distance conveying and high-temperature environments.
A double-liquid grouting material of components A and components B is used. Component A is composed of pozzolan ash characteristic gel material, retarder, expansion agent, low melting point hot melt adhesive and calcium oxide. Component B is composed of polyacrylamide, polyacrylic acid-derived salt, alcohol polysaccharide and water glass. Through the design of retarded expansion particles, the initial settling time is delayed and good thermal stability and high cementitious strength are maintained under high temperature environments.
The grouting material that is initially condensed within 15-30 minutes can maintain good thermal stability and high cementing strength under a high temperature environment of 20-60°C, meeting the water blocking needs in long-distance transportation and high-temperature environments.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of grouting materials, in particular to a high-temperature resistant grouting water blocking material for underground engineering and a preparation method thereof. Background Art
[0002] Grouting water plugging materials in underground projects are key materials used to prevent groundwater leakage, strengthen strata and improve structural stability. Selecting appropriate grouting water plugging materials is crucial to ensure the safety and durability of the project.
[0003] During the grouting process of underground projects, affected by the location of the water blocking point, some projects require long-distance grouting transportation, and the underground ambient temperature is between 40-60°C, which is a high-temperature environment. Under such conditions, the current grouting water blocking materials have the following main shortcomings: (1) The slurry begins to coagulate before reaching the leaking point, which seriously affects the smooth transportation of the slurry and the water blocking effect; (2) The material has poor high temperature resistance, poor thermal stability in an environment of 40-60°C, and the bonding strength does not meet the requirements. Summary of the invention
[0004] The purpose of the present invention is to provide a high-temperature resistant grouting and water-blocking material for underground engineering and a preparation method thereof, so as to overcome the shortcomings of the aforementioned prior art and meet the conditions of long-distance transportation, in which the grouting and water-blocking material begins to solidify rapidly after reaching the leakage point, the initial setting time of the material is between 15-30 minutes, and after solidification, it can maintain good thermal stability in an environment of 20-60°C and has high bonding strength.
[0005] The technical solution adopted by the present invention to solve the technical problem is:
[0006] A high-temperature resistant grouting and water plugging material for underground engineering, comprising component A and component B, wherein component A is mainly composed of the following raw materials in parts by weight: 120-160 parts of a gel material with volcanic ash properties, 4-6 parts of a retarder, 10-15 parts of an expansion agent, 12-18 parts of a low-melting point hot melt adhesive, 20-35 parts of calcium oxide, and 80-100 parts of water; component B is mainly composed of the following raw materials in parts by weight: 3-8 parts of polyacrylamide, 5-10 parts of a polyacrylic acid derivative salt, 1.25-3 parts of an alcohol polysaccharide, 50-120 parts of water glass, and 30-50 parts of water; wherein the expansion agent, the low-melting point hot melt adhesive, the calcium oxide, and 20-30% of the retarder in component A are prepared into slow-setting expansion particles for use, and the preparation method comprises the following steps:
[0007] Under a temperature environment above the melting point of the low-melting-point hot melt adhesive, the expansion agent, the low-melting-point hot melt adhesive, calcium oxide and a retarder with a weight ratio of 20-30% are stirred evenly to form a mixture, and after the mixture is cooled and solidified, it is broken into 2-5 mm particles, and a 0.2-0.3 mm water-soluble polyvinyl alcohol film is coated on the outside of the particles;
[0008] The low melting point hot melt adhesive has a melting point higher than the ambient temperature of the grouting water blocking point and lower than the heat generation temperature of the reaction between calcium oxide and water.
[0009] Preferably, the 0.2-0.3 mm water-soluble polyvinyl alcohol film is an NT type film, and the dissolution time is 25-45 min in an environment of 20-35°C.
[0010] Preferably, the water glass is medium modulus water glass, 2.5≤M≤2.8.
[0011] Preferably, the gel material with pozzolanic properties is prepared by mixing silicate cement and fly ash in a weight ratio of (1-1.5): (3-5).
[0012] Preferably, the retarder is mainly composed of sodium lignin sulfonate and borax in a weight ratio of (2-3):1.
[0013] Preferably, the expansion agent is a compound of cross-linked polyacrylate, sodium dodecyl sulfonate, sodium dodecyl sulfate, aluminum dodecyl sulfate, sodium α-olefin sulfonate, and aluminum powder, with a weight ratio of (0.8-1.2): (0.8-1.2): (0.4-0.8): (0.4-0.8): (20-30): (8-12).
[0014] Preferably, the low melting point hot melt adhesive is one of EVA hot melt adhesive, polyester hot melt adhesive, polyester amide hot melt adhesive, polyolefin hot melt adhesive, and rubber-based hot melt adhesive.
[0015] Preferably, the polyacrylic acid derivative salt is one of sodium polyacrylate, potassium polyacrylate, calcium polyacrylate and zinc polyacrylate.
[0016] Preferably, the alcohol polysaccharide is one of polyethylene glycol-2000, sodium gluconate, sodium alginate and curdlan.
[0017] A method for preparing a high temperature resistant grouting and water plugging material for underground engineering, wherein the method for preparing component A comprises the following steps:
[0018] Preparing slow-setting expansion particles in advance;
[0019] Mix the specified weight proportions of the volcanic ash gel material and water and stir evenly, add the remaining 20-30% of the retarder and continue to mix evenly to form slurry A;
[0020] The slow-setting expansion particles and slurry A are kept aside separately;
[0021] The preparation method of the B component comprises the following steps:
[0022] Mix polyacrylamide, polyacrylic acid derivative salt, alcohol polysaccharide and water in specified weight portions and stir for 5-10 minutes, then add water glass in specified weight portions while mixing, and continue stirring until uniform to form slurry B;
[0023] When using high temperature resistant grouting and water blocking materials for underground projects, component A and component B are grouted with double liquids. Before the double liquid grouting operation, the slow setting expansion particles are put into the slurry A and stirred for 2-3 minutes before use.
[0024] In the components of this material, component A is the main cement-based gel material, and component B is a material that promotes the coagulation of component A and reacts with component A to enhance its coagulation strength.
[0025] The functions of each raw material in component A are:
[0026] The gel material with pozzolanic properties is made of silicate cement and fly ash in a weight ratio of (1-1.5): (3-5). The fly ash accounts for a high proportion, and compared with the slurry with a high proportion of silicate cement, the overall fluidity is good. As the silicate cement is hydrated to produce calcium hydroxide, the fly ash is gradually hydrated under the action of calcium hydroxide and water. Especially when there is a surplus of calcium hydroxide, the fly ash hydration reaction can continue for a long time. Therefore, in the later stage of plugging the water, the strength of the plugging point will continue to increase, showing better long-term performance.
[0027] The gel material with volcanic ash characteristics is stirred with water at a high water-cement ratio, and has good fluidity. Under the influence of the retarder, it is not easy to coagulate prematurely even if the transportation time is as long as 15-30 minutes, and has good fluidity.
[0028] In the retarding expansion particles, the expansion agent, low melting point hot melt adhesive, calcium oxide and a small amount of retarder are mixed and condensed, then broken and coated with a 0.2-0.3mm water-soluble polyvinyl alcohol film. The 0.2-0.3mm water-soluble polyvinyl alcohol film is an NT type film, and the dissolution time is 25-45min in an environment of 20-35℃. During the stirring and conveying process of the retarding expansion particles, the dissolution rate of the water-soluble polyvinyl alcohol film will increase due to the friction between the raw materials and the increase in ambient temperature, and the dissolution time will be shortened to 10-25min. When the retarding expansion particles begin to dissolve, part of the calcium oxide inside them comes into contact with water, and the calcium oxide reacts with water:
[0029] CaO+H2O→Ca(OH)2
[0030] Heat and calcium hydroxide are generated. This reaction process is gradually carried out after the water-soluble polyvinyl alcohol film is exposed and the internal material is exposed. It lasts for 2-5 minutes. Although the heat is not greatly diffused due to the influence of the surrounding environment, it melts the low-melting-point hot melt condensed around it, releasing more calcium oxide, and at the same time releasing the expansion agent and a small amount of retarder. The molecules of the expansion agent have both hydrophilic and hydrophobic groups. Under the action of slurry transportation, calcium oxide reaction, and mixing with the component wall to form turbulence, denser small bubbles will be formed, which will cause the slurry to expand in volume when entering the area to be blocked, thereby increasing its water blocking and sealing effect. The retarder further plays a role in slowing down the solidification after the water-soluble polyvinyl alcohol film is dissolved.
[0031] The functions of each raw material in component B are:
[0032] The modulus of water glass is: 2.5≤M≤2.8, which is a medium to high modulus. It has good adhesion and can promote the high-strength condensation of gel materials with volcanic ash characteristics, but its fluidity is lower than that of water glass with M<2. Adding an appropriate amount of water to component B can promote the fluidity of water glass, adding an appropriate amount of polyacrylamide can promote the fluidity of water glass and improve the stability of water glass, adding an appropriate amount of polyacrylic acid derivative salt can improve the dispersibility of water glass. The appropriate addition and coordination of these raw materials promotes the smooth and stable transportation of water glass with a modulus between 2.5-2.8 for 15-30 minutes to mix with component A.
[0033] Under the double liquid grouting construction process, when component A is mixed with component B, the components impact each other to form a mixing effect. In component A, cement hydrates to form part of calcium hydroxide, while calcium oxide reacts with water to form part of calcium hydroxide. These calcium hydroxides react with water glass to form calcium silicate gel (CSH):
[0034]
[0035] The formation of key products that enhance the strength after setting also maintains the alkaline environment formed by calcium hydroxide and sodium hydroxide, which is essential for preventing steel corrosion and is beneficial to the stability and long-term performance of certain mineral phases (such as CSH gel).
[0036] Since component A contains oil-containing low-melting-point hot-melt adhesive, its melting point is higher than the ambient temperature of the grouting water plugging point and lower than the heat generation temperature of the reaction between calcium oxide and water. Therefore, after the calcium oxide reaction is complete, the low-melting-point hot-melt adhesive will return to a solidified state. Under the action of the force generated by the calcium oxide reaction, the solidified state of the low-melting-point hot-melt adhesive is an irregular shape, which is easy to adhere to and bond to the surrounding structure when the slurry solidifies, thereby improving the overall strength of the structure.
[0037] The beneficial effects of the present invention are as follows: compared with the prior art, the underground engineering high temperature resistant grouting water plugging material and the preparation method thereof of the present invention have the following advantages: both component A and component B have good fluidity, meet the long-distance transmission conditions, and the initial setting time of the material is between 15-30 minutes; under the action of the slow-setting expansion particles, component A starts to release the swelling agent before being transported to mix with component B, which causes the slurry to expand in volume when entering the area to be plugged, thereby increasing its water plugging and sealing effect; after the calcium oxide reaction is complete, the low melting point hot melt adhesive will restore the solidified state, and under the action of the cross-flow force formed by the calcium oxide reaction, the solidified state of the low melting point hot melt adhesive is an irregular shape, and it is easy to adhere to and bond the surrounding structure when the slurry solidifies, thereby improving the overall strength of the structure; an alkaline environment of calcium hydroxide and sodium hydroxide is formed during the mixing process of component A and component B, and this alkaline environment is crucial to preventing steel corrosion, and is beneficial to the stability and long-term performance of certain mineral phases (such as CSH gel); the fly ash hydration reaction can continue for a long time, so in the later stage after the plugging is completed, the strength of the plugging point will continue to increase, showing better long-term performance. DETAILED DESCRIPTION
[0038] Example 1
[0039] A high-temperature resistant grouting and water plugging material for underground engineering, comprising component A and component B, wherein component A is mainly composed of the following raw materials in parts by weight: 140 parts of a gel material with volcanic ash properties, 5 parts of a retarder, 12 parts of an expansion agent, 15 parts of a low-melting point hot melt adhesive, 38 parts of calcium oxide, and 94 parts of water; and component B is mainly composed of the following raw materials in parts by weight: 6 parts of polyacrylamide, 7 parts of a polyacrylic acid derivative salt, 2.38 parts of an alcohol polysaccharide, 88 parts of water glass, and 45 parts of water;
[0040] Among the above raw materials, the gel material with volcanic ash properties is prepared by mixing silicate cement and fly ash in a weight ratio of 1.344:4.2. The retarder is mainly prepared by mixing sodium lignin sulfonate and borax in a weight ratio of 2.6:1. The expansion agent is prepared by mixing cross-linked polyacrylate, sodium dodecyl sulfonate, sodium dodecyl sulfate, aluminum dodecyl sulfate, sodium α-olefin sulfonate, and aluminum powder in a weight ratio of 1:1:0.5:0.8:22:8. The low melting point hot melt adhesive is an EVA type hot melt adhesive. The polyacrylic acid derivative salt is calcium polyacrylate. The alcohol polysaccharide is polyethylene glycol-2000. The water glass is a medium modulus water glass, M=2.6.
[0041] The underground engineering high temperature resistant grouting water blocking material of this embodiment has an ambient temperature of 55-60°C at the water blocking point.
[0042] The melting point of low melting point hot melt adhesive is 80℃.
[0043] In this embodiment, the expansion agent, low melting point hot melt adhesive, calcium oxide and 25% of retarder in component A are prepared into retarded expansion particles for use.
[0044] The preparation method of the underground engineering high temperature resistant grouting water blocking material of this embodiment, the preparation method of the A component comprises the following steps:
[0045] Preparing slow-setting expansion particles in advance, stirring an expansion agent, a low-melting point hot melt adhesive, calcium oxide and a retarder with a weight ratio of 25% at 100° C. to form a mixture, breaking the mixture into 2-5 mm particles after cooling and solidifying, and coating the particles with a 0.3 mm water-soluble polyvinyl alcohol film; the 0.3 mm water-soluble polyvinyl alcohol film is an NT-type film, and the dissolution time at room temperature is 45 minutes;
[0046] Mix the specified weight proportions of the volcanic ash gel material and water and stir to mix evenly, add the remaining 75% of the retarder and continue to stir and mix evenly to form slurry A;
[0047] The slow-setting expansion particles and slurry A are kept aside separately;
[0048] The preparation method of the B component comprises the following steps:
[0049] Mix polyacrylamide, polyacrylic acid derivative salt, alcohol polysaccharide and water in specified weight portions and stir for 8 minutes, then add water glass in specified weight portions while mixing, and continue stirring until uniform to form slurry B;
[0050] When using high temperature resistant grouting and water blocking materials for underground projects, component A and component B are grouted with double liquids. Before the double liquid grouting operation, the slow setting expansion particles are put into the slurry A and stirred for 3 minutes before use.
[0051] When in use, the double-wall drill pipe of the double-liquid grouting system transports component A and component B respectively. It takes about 28 minutes to reach the water blocking point. The ambient temperature is between 55-60℃. Component A and component B can be initially solidified in about 1 minute at the water blocking point. The compressive strength of the stone body is 1.5MPa in the 1d solidification period, 6MPa in the 3d solidification period, and 14MPa in the 10d solidification period.
[0052] Example 2
[0053] A high-temperature resistant grouting and water plugging material for underground engineering, comprising component A and component B, wherein component A is mainly composed of the following raw materials in parts by weight: 120 parts of a gel material with volcanic ash properties, 4 parts of a retarder, 10 parts of an expansion agent, 12 parts of a low-melting point hot melt adhesive, 20 parts of calcium oxide, and 80 parts of water; and component B is mainly composed of the following raw materials in parts by weight: 3 parts of polyacrylamide, 5 parts of a polyacrylic acid derivative salt, 1.25 parts of an alcohol polysaccharide, 50 parts of water glass, and 30 parts of water;
[0054] Among the above raw materials, the gel material with volcanic ash properties is prepared by mixing silicate cement and fly ash in a weight ratio of 1:3.2. The retarder is mainly prepared by mixing sodium lignin sulfonate and borax in a weight ratio of 2:1. The expansion agent is prepared by mixing cross-linked polyacrylate, sodium dodecyl sulfonate, sodium dodecyl sulfate, aluminum dodecyl sulfate, sodium α-olefin sulfonate and aluminum powder in a weight ratio of 1:1:0.7:0.75:28:8. The low melting point hot melt adhesive is a polyester hot melt adhesive. The polyacrylic acid derivative salt is sodium polyacrylate. The alcohol polysaccharide is sodium alginate. The water glass is a medium modulus water glass, M=2.5.
[0055] The underground engineering high temperature resistant grouting water blocking material of this embodiment has an ambient temperature of 40-45°C at the water blocking point.
[0056] The melting point of low melting point hot melt adhesive is 85℃.
[0057] In this embodiment, the expansion agent, low melting point hot melt adhesive, calcium oxide and 20% retarder in component A are prepared into retarded expansion particles for use.
[0058] The preparation method of the underground engineering high temperature resistant grouting water blocking material of this embodiment, the preparation method of the A component comprises the following steps:
[0059] Preparing slow-setting expansion particles in advance, stirring an expansion agent, a low-melting point hot melt adhesive, calcium oxide and a retarder with a weight ratio of 20% at 100° C. to form a mixture, breaking the mixture into 2-5 mm particles after cooling and solidifying, and coating the particles with a 0.2 mm water-soluble polyvinyl alcohol film, wherein the 0.2 mm water-soluble polyvinyl alcohol film is an NT type film, and the dissolution time at room temperature is 25 min;
[0060] The volcanic ash gel material and water in the prescribed weight proportions are mixed and stirred evenly, and the remaining 80% of the retarder is added and continued to be mixed evenly to form slurry A;
[0061] The slow-setting expansion particles and slurry A are kept aside separately;
[0062] The preparation method of the B component comprises the following steps:
[0063] Mix polyacrylamide, polyacrylic acid derivative salt, alcohol polysaccharide and water in specified weight portions and stir for 5 minutes, then add water glass in specified weight portions while mixing, and continue stirring until uniform to form slurry B;
[0064] When using high temperature resistant grouting and water blocking materials for underground projects, component A and component B are grouted with double liquids. Before the double liquid grouting operation, the slow setting expansion particles are put into the slurry A and stirred for 2 minutes before use.
[0065] When in use, the double-wall drill pipe of the double-liquid grouting system transports component A and component B respectively. It takes about 13 minutes to reach the water blocking point. The ambient temperature is between 40-45°C. Component A and component B can be initially solidified in about 1 minute at the water blocking point. The compressive strength of the stone body is 1.2MPa in the 1d solidification period, 4.5MPa in the 3d solidification period, and 12MPa in the 10d solidification period.
[0066] Example 3
[0067] A high-temperature resistant grouting and water plugging material for underground engineering, comprising component A and component B, wherein component A is mainly composed of the following raw materials in parts by weight: 160 parts of a gel material with volcanic ash properties, 6 parts of a retarder, 15 parts of an expansion agent, 18 parts of a low-melting point hot melt adhesive, 35 parts of calcium oxide, and 100 parts of water; and component B is mainly composed of the following raw materials in parts by weight: 8 parts of polyacrylamide, 10 parts of a polyacrylic acid derivative salt, 3 parts of an alcohol polysaccharide, 120 parts of water glass, and 50 parts of water.
[0068] Among the above raw materials, the gel material with volcanic ash properties is prepared by mixing silicate cement and fly ash in a weight ratio of 1.5:5. The retarder is mainly prepared by mixing sodium lignin sulfonate and borax in a weight ratio of 3:1. The expansion agent is prepared by mixing cross-linked polyacrylate, sodium dodecyl sulfonate, sodium dodecyl sulfate, aluminum dodecyl sulfate, sodium α-olefin sulfonate and aluminum powder in a weight ratio of 1:1:0.5:0.6:20:11. The low melting point hot melt adhesive is a polyester amide hot melt adhesive. The polyacrylic acid derivative salt is calcium polyacrylate. The alcohol polysaccharide is sodium gluconate. The water glass is a medium modulus water glass, M=2.8.
[0069] The underground engineering high temperature resistant grouting water blocking material of this embodiment has an ambient temperature of 45-55°C at the water blocking point.
[0070] The melting point of low melting point hot melt adhesive is 85℃.
[0071] In this embodiment, the expansion agent, low melting point hot melt adhesive, calcium oxide and 30% of retarder in component A are prepared into retarded expansion particles for use.
[0072] The preparation method of the underground engineering high temperature resistant grouting water blocking material of this embodiment, the preparation method of the A component comprises the following steps:
[0073] Prepare slow-setting expansion particles in advance, and stir the expansion agent, low-melting point hot melt adhesive, calcium oxide and 30% by weight of retarder in an environment of 100°C to form a mixture. After the mixture is cooled and solidified, it is broken into 2-5 mm particles, and the outside of the particles is covered with a 0.3 mm water-soluble polyvinyl alcohol film; the 0.3 mm water-soluble polyvinyl alcohol film is an NT type film, and the dissolution time at room temperature is 45 minutes.
[0074] The volcanic ash gel material and water in the prescribed weight proportions are mixed and stirred evenly, and the remaining 70% of the retarder is added and continued to be mixed evenly to form slurry A;
[0075] The slow-setting expansion particles and slurry A are kept aside separately;
[0076] The preparation method of the B component comprises the following steps:
[0077] Mix polyacrylamide, polyacrylic acid derivative salt, alcohol polysaccharide and water in specified weight portions and stir for 10 minutes, then add water glass in specified weight portions while mixing, and continue stirring until uniform to form slurry B;
[0078] When using high temperature resistant grouting and water blocking materials for underground projects, component A and component B are grouted with double liquids. Before the double liquid grouting operation, the slow setting expansion particles are put into the slurry A and stirred for 3 minutes before use.
[0079] When in use, the double-wall drill pipe of the double-liquid grouting system transports component A and component B respectively. It takes about 20 minutes to reach the water blocking point. The ambient temperature is between 45-55°C. Component A and component B can be initially solidified in about 1 minute at the water blocking point. The compressive strength of the stone body is 1.4MPa in the 1d solidification period, 5.5MPa in the 3d solidification period, and 13MPa in the 10d solidification period.
[0080] Example 4
[0081] A high-temperature resistant grouting and water plugging material for underground engineering, comprising component A and component B, wherein component A is mainly composed of the following raw materials in parts by weight: 140 parts of a gel material with volcanic ash properties, 5 parts of a retarder, 12 parts of an expansion agent, 15 parts of a low-melting point hot melt adhesive, 38 parts of calcium oxide, and 94 parts of water; and component B is mainly composed of the following raw materials in parts by weight: 6 parts of polyacrylamide, 7 parts of a polyacrylic acid derivative salt, 2.38 parts of an alcohol polysaccharide, 88 parts of water glass, and 45 parts of water;
[0082] Among the above raw materials, the gel material with volcanic ash properties is prepared by mixing silicate cement and fly ash in a weight ratio of 1.344:4.2. The retarder is mainly prepared by mixing sodium lignin sulfonate and borax in a weight ratio of 2.6:1. The expansion agent is prepared by mixing cross-linked polyacrylate, sodium dodecyl sulfonate, sodium dodecyl sulfate, aluminum dodecyl sulfate, sodium α-olefin sulfonate, and aluminum powder in a weight ratio of 1:1:0.5:0.8:22:8. The low melting point hot melt adhesive is an EVA type hot melt adhesive. The polyacrylic acid derivative salt is calcium polyacrylate. The alcohol polysaccharide is polyethylene glycol-2000. The water glass is a medium modulus water glass, M=2.6.
[0083] The ambient temperature of the underground engineering high temperature resistant grouting water blocking material in this embodiment is the same as that in embodiment 1, which is 55-60°C.
[0084] The melting point of low melting point hot melt adhesive is 80℃.
[0085] The preparation method of the underground engineering high temperature resistant grouting water blocking material of this embodiment, the preparation method of the A component comprises the following steps:
[0086] Stir the expansion agent, low melting point hot melt adhesive, calcium oxide and retarder evenly to form an additive mixture;
[0087] Mixing a specified weight portion of a volcanic ash gel material and water, stirring and mixing, adding the auxiliary agent mixture, and continuing to stir and mix to form a slurry A;
[0088] The preparation method of the B component comprises the following steps:
[0089] Mix polyacrylamide, polyacrylic acid derivative salt, alcohol polysaccharide and water in specified weight portions and stir for 8 minutes, then add water glass in specified weight portions while mixing, and continue stirring until uniform to form slurry B;
[0090] When using high temperature resistant grouting water blocking materials for underground projects, double liquid grouting is used for component A and component B. Component A and component B are transported separately through the double-wall drill pipe of the double liquid grouting system.
[0091] During the transportation process, when component A was transported to the middle and rear sections, the slurry solidified prematurely and caused blockage. The grouting operation was immediately stopped on site, all related valves and pumping devices were closed, and unblocking operations were performed. The cause of the blockage was analyzed as follows: the expansion agent reacted prematurely, the slurry expanded, and calcium oxide reacted with water prematurely to form calcium hydroxide. In the early stage of transportation, calcium hydroxide reduced the van der Waals force and other attractive forces between the slurry particles and reduced the agglomeration of particles. However, its force was weakened under long-distance transportation conditions, and slurry A began to solidify prematurely.
[0092] The above-mentioned specific implementations are only specific cases of the present invention. The patent protection scope of the present invention includes but is not limited to the product form and style of the above-mentioned specific implementations. Any appropriate changes or modifications made to them by ordinary technicians in the technical field that conform to the claims of the present invention shall fall within the patent protection scope of the present invention.
Claims
1. A high temperature resistant grouting water blocking material for underground engineering, characterized in that: The invention comprises component A and component B, wherein component A is mainly composed of the following raw materials in parts by weight: 120-160 parts of gel material with volcanic ash properties, 4-6 parts of retarder, 10-15 parts of expansion agent, 12-18 parts of low melting point hot melt adhesive, 20-35 parts of calcium oxide, and 80-100 parts of water; component B is mainly composed of the following raw materials in parts by weight: 3-8 parts of polyacrylamide, 5-10 parts of polyacrylic acid derivative salt, 1.25-3 parts of alcohol polysaccharide, 50-120 parts of water glass, and 30-50 parts of water; wherein the expansion agent, low melting point hot melt adhesive, calcium oxide, and 20-30% of retarder in component A are prepared into slow-setting expansion particles for use, and the preparation method comprises the following steps: Under a temperature environment above the melting point of the low-melting-point hot melt adhesive, the expansion agent, the low-melting-point hot melt adhesive, calcium oxide and a retarder with a weight ratio of 20-30% are stirred evenly to form a mixture, and after the mixture is cooled and solidified, it is broken into 2-5 mm particles, and a 0.2-0.3 mm water-soluble polyvinyl alcohol film is coated on the outside of the particles; The low melting point hot melt adhesive has a melting point higher than the ambient temperature of the grouting water blocking point and lower than the heat generation temperature of the reaction between calcium oxide and water.
2. The high temperature resistant grouting water blocking material for underground engineering according to claim 1, characterized in that: The 0.2-0.3 mm water-soluble polyvinyl alcohol film is an NT type film, and the dissolution time is 25-45 minutes in an environment of 20-35°C.
3. The high temperature resistant grouting water blocking material for underground engineering according to claim 1, characterized in that: The water glass is a medium modulus water glass, 2.5≤M≤2.
8.
4. The high temperature resistant grouting water blocking material for underground engineering according to claim 1, characterized in that: The gel material with pozzolanic properties is prepared by mixing silicate cement and fly ash in a weight ratio of (1-1.5): (3-5).
5. The high temperature resistant grouting water blocking material for underground engineering according to claim 1, characterized in that: The retarder is mainly prepared by mixing sodium lignin sulfonate and borax in a weight ratio of (2-3):
1.
6. The high temperature resistant grouting water blocking material for underground engineering according to claim 1, characterized in that: The expansion agent is mainly prepared by compounding multiple of cross-linked polyacrylate, sodium dodecyl sulfonate, sodium dodecyl sulfate, aluminum dodecyl sulfate, sodium α-olefin sulfonate and aluminum powder.
7. The high temperature resistant grouting water blocking material for underground engineering according to claim 1, characterized in that: The low melting point hot melt adhesive is one of EVA hot melt adhesive, polyester hot melt adhesive, polyester amide hot melt adhesive, polyolefin hot melt adhesive, and rubber-based hot melt adhesive.
8. The high temperature resistant grouting water blocking material for underground engineering according to claim 1, characterized in that: The polyacrylic acid derivative salt is one of sodium polyacrylate, potassium polyacrylate, calcium polyacrylate and zinc polyacrylate.
9. The high temperature resistant grouting water blocking material for underground engineering according to claim 1, characterized in that: The alcohol polysaccharide is one of polyethylene glycol-2000, sodium gluconate, sodium alginate and curdlan.
10. A method for preparing a high temperature resistant grouting and water blocking material for underground engineering according to any one of claims 1 to 9, characterized in that: The preparation method of the A component comprises the following steps: Preparing slow-setting expansion particles in advance; Mix the specified weight proportions of the volcanic ash gel material and water and stir evenly, add the remaining 20-30% of the retarder and continue to mix evenly to form slurry A; The slow-setting expansion particles and slurry A are kept aside separately; The preparation method of the B component comprises the following steps: Mix polyacrylamide, polyacrylic acid derivative salt, alcohol polysaccharide and water in specified weight portions and stir for 5-10 minutes, then add water glass in specified weight portions while mixing, and continue stirring until uniform to form slurry B; When using high temperature resistant grouting and water blocking materials for underground projects, component A and component B are grouted with double liquids. Before the double liquid grouting operation, the slow setting expansion particles are put into the slurry A and stirred for 2-3 minutes before use.
Citation Information
Patent Citations
Early-strength expansion delayed type hole sealing material
CN107651905A
Delayed expansion type composite drilling sealing material
CN110627440A
Mining hole sealing curing expansion material
CN114873966A
Pump concrete prepared from concrete residues and preparation method thereof
CN115196918A
Coastal karst cement-based gelling expansion grouting material and preparation method thereof
CN115215607A
Cited By
Low-temperature inorganic grouting reinforcement material as well as production equipment and processing method thereof
CN120622903A
Dispersion-resistant micro-expansion grouting material in dynamic water environment and preparation method thereof
CN120923199A